Clinical Approach to Vascular Calcification in Patients With Non-dialysis Dependent Chronic Kidney Disease: Mineral-Bone Disorder-Related Aspects - Bover, Jordi; Aguilar, Armando; Arana, Carolt; Molina, Pablo; Lloret, María Jesús; Ochoa, Jackson; Berná, Gerson; Gutiérrez-Maza, Yessica G.; Rodrigues, Natacha; D'Marco, Luis; Górriz, José L. (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) is associated with a very high morbimortality, mainly from cardiovascular origin, and CKD is currently considered in the high- or very high risk- cardiovascular risk category. CKD-mineral and bone disorders (CKD-MBDs), including vascular and/or valvular calcifications, are also associated with these poor outcomes. Vascular calcification (VC) is very prevalent (both intimal and medial), even in non-dialysis dependent patients, with a greater severity and more rapid progression. Simple X-ray based-scores such as Adragão's (AS) are useful prognostic tools and AS (even AS based on hand-X-ray only) may be superior to the classic Kauppila's score when evaluating non-dialysis CKD patients. Thus, in this mini-review, we briefly review CKD-MBD-related aspects of VC and its complex pathophysiology including the vast array of contributors and inhibitors. Furthermore, although VC is a surrogate marker and is not yet considered a treatment target, we consider that the presence of VC may be relevant in guiding therapeutic interventions, unless all patients are treated with the mindset of reducing the incidence or progression of VC with the currently available armamentarium. Avoiding phosphate loading, restricting calcium-based phosphate binders and high doses of vitamin D, and avoiding normalizing (within the normal limits for the assay) parathyroid hormone levels seem logical approaches. The availability of new drugs and future studies, including patients in early stages of CKD, may lead to significant improvements not only in patient risk stratification but also in attenuating the accelerated progression of VC in CKD.